Safety Pharmacology - Risk Assessment QT Interval Prolongation and Beyond - Stefano Morotti (Frontiers Research Topics, 2018)
Current regulatory guidelines for cardiac safety utilize hERG block and QT interval prolongation as risk markers. This strategy has been successful at preventing harmful drugs from being marketed, but criticized for leading to early withdrawal of potentially safe drugs. Here we collected a series of articles presenting new technological and conceptual advances, including refinement of ex vivo and in vitro assays, screens and models, and in silico approaches reflecting the increasing effort that has been put forward by regulatory agencies, industry, and academia to try and address the need of a more accurate, mechanistically-based paradigm of proarrhythmic potential of drugs. This Research Topic is dedicated to the memory of Dr. J. Jeremy Rice, our wonderful friend and colleague.